Digital agroclimatic plot in Guatemala's dry corridor: Progress, learning, and innovation for agricultural decision-making - Ramos, Gresia; Lizarazo, Miguel; Jimenez, Daniel; Estrada, Oscar (2025)
The Digital Agroclimatic Plot in Guatemala’s Dry Corridor represents an innovative approach to strengthening agricultural decision-making in highly climate-vulnerable contexts. Conceived in 2022 and operationalized in 2023 with the support of the strategic local partner Centro Universitario de Oriente (CUNORI) in Chiquimula, the plot functions as a living laboratory that integrates agroclimatic data, field experimentation, and digital tools. It serves a diverse group of users, including university students and faculty, local farmers, field technicians, and researchers, fostering knowledge exchange and applied learning. This working paper documents the trajectory of the Digital Agroclimatic Plot, highlighting its scope, key results, and contributions to innovation in the region. By bridging research, education, and practice, the Digital Agroclimatic Plot demonstrates the potential of participatory, data-driven platforms to enhance resilience and adaptive capacity in Guatemala’s Dry Corridor.